The Problem of Deviant Casual Chains - Amen, Miguel (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2005)
In the following article I identify the source of Davidson's failure to provide an analysis of intentional action. It is shown that this failure should be seen as an instance of consistency within his overall theory of mind and action. In Actions, Reason and Causes (1963) Davidson defended the causal theory of action, according to which the intentions for which a person acts are the reasons for which he acts and those reasons cause the action. According to Davidson, a reason for an action A consists in the agent having a pro-attitude toward actions of a certain kind along with a belief that Aing is an action of that kind. Pro-attitudes can be seen as desires and wantings, giving goals and motives for action.